High current, long-pulse operation at the KEK superconducting rf test facility - Masakazu Kurata; Toshihiro Matsumoto; Masafumi Fukuda; Yasuchika Yamamoto; Hitoshi Hayano; Shinichiro Michizono; Yoshihisa Iwashita (Physical Review Accelerators and Beams)
A high-current, long-pulsed beam operation without beam loss was demonstrated at the Superconducting rf Test Facility (STF) of the High Energy Accelerator Research Organization. The primary purpose of the STF was to validate the superconducting radio-frequency (rf) acceleration technology for the International Linear Collider (ILC) using accelerator components in line with the ILC design. Thus, the most critical objective of STF was to perform beam operations with a pulse length (726-μsec) and current (5.8 mA) equal to those of the ILC. Severe radiation caused by beam loss hinders stable beam operation. In a 100-μsec pulsed beam operation, a gradient drop in the accelerating cavities owing to beam loading causes beam loss. This beam loading was suppressed by imposing an additional driving power as feedforward control (BeamFF) to compensate for the gradient drop. BeamFF can completely suppress the gradient variation from a flattop to a 0.4% level with an amplitude stability of 0.3%–0.4%. Based on the knowledge obtained in the 100-μsec beam operation, we achieved a stable 726-μsec, 5.8-mA beam operation, and a beam power of 5.6 kW. The maximum energy variation of the pulsed beam was 1.5%. This value is significantly less than the threshold of 4%, which causes beam loss. We thus verified the stable beam acceleration technology for the ILC at the STF.